Analisis Pengaruh Sektor Pengangkutan dan Komunikasi terhadap Pertumbuhan Ekonomi Kota Banyuwangi Tahun 2010-2014 (PDRB) - Wahyudi Setiawan; Rafael Purtomo S; Andjar Widjajanti (UPT Penerbitan Universitas Jember, 2017)
Transport and communications sector is have a the direct and un-directly linkage behind the upstream industry andalso gives the best impact on output generated by Banyuwangi. The purpose of this study was to determine the effect ofthe development of the transport and communications sector to economic growth in the city of Banyuwangi and conductforecasting the development of economic growth in the city of Banyuwangi if the review of the transport andcommunications sector. This research is a non-survey study with explanatory method, namely the search for large,there is not and how the pattern of relationships between two or more variables. Unit research used in this study is theperformance of the transport and communications sector to the Gross Regional Domestic Product (GRDP) andeconomic growth of the city of Banyuwangi in 2010-2014. These analysis are simple linear regression and trendanalysis with regression approach. The result showed that the development of the transport and communications sectorto economic growth in the city of Banyuwangi showed a positive development trend in 2010-2014 with an upward trendfrom year to year. Transport and communications sector performance significantly affect economic growth in the cityof Banyuwangi with a value of 37.964 t-test and significance value of 0.000. Forecasting the performance of thetransport and communications sector, the development of Gross Regional Domestic Product (GRDP) and economicgrowth Banyuwangi in 2015 showed improved results compared to previous years, with the value of the transport andcommunications sector performance amounted to 654,689.34 million, Gross Regional Domestic Product (GRDP) of15,095,868.203 million and an economic growth of 5.92%.